2019
DOI: 10.18203/2319-2003.ijbcp20192569
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adverse drug reactions: a study in a tertiary care

Abstract: Background: Adverse drug reaction, usually reported by pharmacovigilance, either through health care professionals or the patients themselves is of utmost importance to give an accurate estimate of the severity of the drug and also if the ADRs are casual, preventable or severe.Methods: A total of 42 patients satisfied the WHO definition of ‘adverse drug reactions’ were included in the study. The demographic details were taken, and the regular physical examination and clinical examination was done for all the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…This was also observed in study done by Raja and Venkatasubbaiah et al 13,14 In this study, skin and appendages constituted the most common system affected, accounting for (59.2%) of total ADRs reported with the predominant symptom being skin rashes seen in 44 (31.7%) of the patients, urticaria in 10 (7.2%). This is in congruence with studies conducted earlier by Kumar et al and Bhabhor et al 2,15 However, Abhishake et al, and Sajin et al, reported different results, documenting gastrointestinal problems to be 39% and 33%, respectively, being most prevalent manifestation among patients with reported ADR. 3,16 General was the next most common system affected in this study, total reported ADRs were (19.4%) with 15 (10.8%) having anaphylaxis, 12 (8.6%) had hypersensitivity reaction and 3 (2.2%) had fever with chills.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was also observed in study done by Raja and Venkatasubbaiah et al 13,14 In this study, skin and appendages constituted the most common system affected, accounting for (59.2%) of total ADRs reported with the predominant symptom being skin rashes seen in 44 (31.7%) of the patients, urticaria in 10 (7.2%). This is in congruence with studies conducted earlier by Kumar et al and Bhabhor et al 2,15 However, Abhishake et al, and Sajin et al, reported different results, documenting gastrointestinal problems to be 39% and 33%, respectively, being most prevalent manifestation among patients with reported ADR. 3,16 General was the next most common system affected in this study, total reported ADRs were (19.4%) with 15 (10.8%) having anaphylaxis, 12 (8.6%) had hypersensitivity reaction and 3 (2.2%) had fever with chills.…”
Section: Discussionsupporting
confidence: 90%
“…Adverse drug reaction has been described by the WHO as a "noxious, unintended and undesired effect of a drug, which occur at doses used in humans for prophylaxis, diagnosis or cure of a disease." 2 Every time the patient is exposed to a new medication, the risk of Adverse drug reactions (ADRs) is present, as we cannot predict the incidence. Thus, no drug is absolutely safe, even when prescribed in therapeutic doses.…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with our study's findings, where antimicrobials, specifically antibiotics, were the most frequently reported culprits 26 . Research studies indicate that non-compliance accounted for 46.6% of drug-related hospitalizations, with ADRs and drug overdose being the primary reasons for drug-related incidents 27 . In our study, 11.32% of DRPs were due to drug use without indication, predominantly associated with multivitamins.…”
Section: Resultsmentioning
confidence: 99%